2015
DOI: 10.4028/www.scientific.net/amm.773-774.8
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Melt Flow Index on Copper-ABS for Fused Deposition Modeling (FDM) Feedstock

Abstract: Abstract. This paper presents of Polymer Matrix Composite (PMC) as feedstock used in Fused Deposition Modelling(FDM) machine. This study discussed on the development of a new PMC material by the injection molding machine. The material consist of copper powder filled in an acrylonitrile butadiene styrene (ABS), binder and surfactant material. The effect of metal filled in ABS and binder content was investigated experimentally by the Melt Flow Index (MFI) machine. Based on the result obtained, an increment of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The addition of these composites allows for the increase in the melt viscosity allowing layering of the materials as it exits the nozzle. The melt viscosity of the materials plays a large role in the dimensional accuracy and layer resolution of the printed part . The layer integration of each layer is affected due to the particulates disrupting chain entanglement.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of these composites allows for the increase in the melt viscosity allowing layering of the materials as it exits the nozzle. The melt viscosity of the materials plays a large role in the dimensional accuracy and layer resolution of the printed part . The layer integration of each layer is affected due to the particulates disrupting chain entanglement.…”
Section: Methodsmentioning
confidence: 99%
“…The melt viscosity of the materials plays a large role in the dimensional accuracy and layer resolution of the printed part. 44 The layer integration of each layer is affected due to the particulates disrupting chain entanglement. The addition of composites has also been used in conjunction with PLA using natural fibers such as enzymedigested cellulose and wood pulp.…”
Section: D Printing Technologymentioning
confidence: 99%
“…From the point of view of the material, the acrylonitrile-butadiene-styrene copolymer (ABS) is known for its excellent mechanical and impact strengths, dimensional stability, good chemical resistance, low water absorption and high filling capacity, arising as a popular thermoplastic material of choice for FDM applications as it offers satisfactory processability and a relatively low melting temperature [5,[26][27][28][29]. The manufacturing of ABS composites through additive manufacturing (AM) techniques, such as FDM, has been demonstrated [30][31][32][33][34], and melt flow index (MFI) analysis has been a popular testing choice to evaluate the flow behaviour trends of ABS composites developed for 3D printing [35][36][37][38][39][40][41]. Isa et al (2015) [35] and Sa'ude et al (2016) [36] studied the behaviour of ABS/copper composites, and Kumar et al (2019) [38] carried out similar work on ABS/aluminium composites, with all of them targeting the development of materials for extrusion-based AM processes; nonetheless, their results indicated that the filler has distinct effects on MFI depending on its content, suggesting that there would be no direct dependence between the loading content and MFI.…”
Section: Introductionmentioning
confidence: 99%
“…The manufacturing of ABS composites through additive manufacturing (AM) techniques, such as FDM, has been demonstrated [30][31][32][33][34], and melt flow index (MFI) analysis has been a popular testing choice to evaluate the flow behaviour trends of ABS composites developed for 3D printing [35][36][37][38][39][40][41]. Isa et al (2015) [35] and Sa'ude et al (2016) [36] studied the behaviour of ABS/copper composites, and Kumar et al (2019) [38] carried out similar work on ABS/aluminium composites, with all of them targeting the development of materials for extrusion-based AM processes; nonetheless, their results indicated that the filler has distinct effects on MFI depending on its content, suggesting that there would be no direct dependence between the loading content and MFI. However, only knowing a material's MFI is insufficient to process it, since this type of measurement represents the flow of a material under the pressure applied during its testing, and it does not encompass considerations due to shear conditions a polymer chain will be subjected to as it undergoes the processing stage [42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…Novel PLA and ABS filaments are the most commonly used FDM materials. In addition, they have been used as core materials [ 5 , 10 , 11 , 12 ] and also composites [ 13 ]. Their good properties for FDM are low melting temperature, good flow, and rather good mechanical properties.…”
Section: Introductionmentioning
confidence: 99%